2020
DOI: 10.1021/acsbiomaterials.0c00119
|View full text |Cite
|
Sign up to set email alerts
|

Cells-Grab-on Particles: A Novel Approach to Control Cell Focal Adhesion on Hybrid Thermally Annealed Hydrogels

Abstract: Biomaterials engineered with specific cell binding sites, tunable mechanical properties, and complex architectures are essential to control cell adhesion and proliferation. The influence of the local properties, such as the local hardness and stability on the interaction with cells, has not been yet fully understood and exploited. This is particularly relevant for hydrogels, very promising materials with, unfortunately, poor cell adhesion properties, attributed mostly to their softness. Here, we propose a new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 73 publications
2
38
0
Order By: Relevance
“…Deposition of calcium phosphate may increase the stiffness of the sample surface as was show in the similar case with MC3T3‐E1 cells in work. [ 35 ] The second factor is HA that may serve as a source of the Ca 2+ and PO 4 3− for cells and accelerates their proliferation. [ 36–39 ] The cell density is about 30 times higher on the HA rings compared with the agar gel taken as a control one (Figure 7j).…”
Section: Resultsmentioning
confidence: 99%
“…Deposition of calcium phosphate may increase the stiffness of the sample surface as was show in the similar case with MC3T3‐E1 cells in work. [ 35 ] The second factor is HA that may serve as a source of the Ca 2+ and PO 4 3− for cells and accelerates their proliferation. [ 36–39 ] The cell density is about 30 times higher on the HA rings compared with the agar gel taken as a control one (Figure 7j).…”
Section: Resultsmentioning
confidence: 99%
“…For example, it is possible to design hybrid materials [11] by incorporating various particles or networks [27], for example, microcapsules [28], bioglass particles [29], hydroxyapatite particles [30,31] calcium, and magnesium carbonate particles [32][33][34][35]. In this case, it is identified that the cell senses the environment and literally "grabs" hard particles at surfaces [33]. An overview of various interfaces allows us to conclude that many particles incorporated into polymeric coatings can promote cell adhesion [36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, this study implies a significant novelty in the field, as no similar gels with this complexity have been designed or characterized before. We hypothesized that cell interaction can be established by functionalizing the coatings with proteins [ 43 ], while particles in hydrogel coatings can serve for establishing focal adhesion [ 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%